Comparative Analysis of Cellulophaga algicola and Flavobacterium johnsoniae Gliding Motility - Zhu, Yongtao (J Bacteriol, 2016)
Gliding motility is common in members of the phylum Bacteroidetes, including Flavobacterium johnsoniae and Cellulophaga algicola. F. johnsoniae gliding has been extensively studied and involves rapid movement of the cell surface adhesin SprB. Genetic analysis of C. algicola allowed a comparative analysis of gliding. Sixty-three HimarEm1-induced mutants that formed nonspreading colonies were characterized. Each had an insertion in an ortholog of an F. johnsoniae motility gene, highlighting similarities between the motility systems. Differences were also observed. C. algicola lacks orthologs of the F. johnsoniae motility genes gldA, gldF, and gldG that are thought to encode the components of an ATP-binding cassette (ABC) transporter. In addition, mutations in any of 12 F. johnsoniae gld genes result in complete loss of motility, whereas all C. algicola gld mutants retained slight residual motility. This may indicate that C. algicola has multiple motility systems, that the motility proteins exhibit partial redundancy of function, or that essential components of the motility machinery of both C. algicola and F. johnsoniae remain to be discovered. IMPORTANCE The development of genetic tools for C. algicola and comparative analysis of F. johnsoniae and C. algicola motility mutants identified similarities and differences between their gliding motility machineries. Gliding motility is common in the phylum Bacteroidetes. Proteins that are important for gliding in both C. algicola and F. johnsoniae are potential core components of the Bacteroidetes gliding motility machinery.